2009
DOI: 10.1111/j.1365-2184.2009.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cells secrete soluble factors that inhibit cancer cell growth

Abstract: Our findings provide evidence that the human embryonic microenvironment contains soluble factor(s) that are capable of inhibiting growth of cancer cells, and that exposure to such factors may represent a new cancer treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…In their study, cancer cell proliferation decreases after exposure to human ES cell-conditioned media as compared to the controls containing mouse fibroblast conditioned media and normal cancer cell media. Dilution studies demonstrated that depletion of nutrients in human ES cell-conditioned medium does not contribute to the arrest of cancer cell proliferation [21]. This study confirms that hES cells secrete factors smaller than 10 kD which plays a major role in inhibiting cell proliferation and terminating the cell cycle.…”
Section: Embryonic Microenvironment and Cancersupporting
confidence: 63%
“…In their study, cancer cell proliferation decreases after exposure to human ES cell-conditioned media as compared to the controls containing mouse fibroblast conditioned media and normal cancer cell media. Dilution studies demonstrated that depletion of nutrients in human ES cell-conditioned medium does not contribute to the arrest of cancer cell proliferation [21]. This study confirms that hES cells secrete factors smaller than 10 kD which plays a major role in inhibiting cell proliferation and terminating the cell cycle.…”
Section: Embryonic Microenvironment and Cancersupporting
confidence: 63%
“…These effects were not seen when these cells were cultured in hESCs-conditioned medium (hESCs-CM) [15, 18, 19]. In contrast, other studies reported that the exposure of cancer cells to hESCs-CM inhibited their tumorigenicity due to reduced proliferation and increased apoptosis [20]. In the present study we sought to determine the origin of the factors involved in these antitumorigenic effects.…”
Section: Introductionmentioning
confidence: 95%
“…For examples, MSCs secreted various trophic factors to modulate the immune response and cell survival [107] . PSCs have also been shown to self-regulate the expansion and differentiation through autocrine/paracrine signaling such as Wnt, lefty, and Activin A [108][109][110][111][112] . For hematopoietic differentiation, the secreted VEGF, stem cell factor (SCF) and anti-apoptotic factors from ESCs stimulated the formation of colony-forming cells [113] .…”
Section: Outlet Portsmentioning
confidence: 99%